The circumstances surrounding the death of 105 elders as a result of resident-to-resident incidents in dementia in long-term care homes. Issue 4 (8th August 2018) - Caspi, Eilon
ABSTRACT: Resident-to-resident incidents in dementia in long-term care homes resulting in deaths represent a growing concern among residents, family members, care providers, care advocacy organizations, and policy makers. Despite these concerns and experts' predictions by which injurious and fatal incidents will increase in the coming years due to the projected growth in the number of people with dementia, no studies have been conducted in North America on these fatal incidents. This exploratory pilot study makes first steps towards bridging this major gap in research and practice. Using publicly available information (primarily newspaper articles and death review reports), practically useful patterns were identified pertaining to the circumstances surrounding the death of 105 elders as a result of these incidents. The findings could inform various efforts to prevent future deaths in similar circumstances, keep vulnerable and frail residents safe, and encourage researchers to examine risk and protective factors for these incidents.